1988
DOI: 10.1084/jem.167.4.1341
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that activated mucosal T cells play a role in the pathogenesis of enteropathy in human small intestine.

Abstract: Intestinal damage as a result of allergy and infection is a major cause of morbidity in man and animals (1-3). In intestinal allergy the most commonly seen lesions are small intestinal villous atrophy and crypt cell hyperplasia resulting in malabsorption due to a decreased intestinal absorptive surface and decreased digestive enzyme levels in the epithelial cells. The mechanisms involved in these changes in man are not known, but there is evidence from experimental animal studies that T cells may play an impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
181
2
5

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(193 citation statements)
references
References 14 publications
(12 reference statements)
5
181
2
5
Order By: Relevance
“…Several studies have reported that mucosal injury, pathologically similar to that seen in coeliac disease, can be induced experimentally in the intestinal mucosa by T cell activation [17][18][19] or by cytokines that are produced by T cells and monocytes/ macrophages (e.g. tumour necrosis factor-alpha (TNF-), interferon-gamma (IFN-), IL-1, IL-4) [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that mucosal injury, pathologically similar to that seen in coeliac disease, can be induced experimentally in the intestinal mucosa by T cell activation [17][18][19] or by cytokines that are produced by T cells and monocytes/ macrophages (e.g. tumour necrosis factor-alpha (TNF-), interferon-gamma (IFN-), IL-1, IL-4) [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…However, several gastrointestinal diseases show pathologic changes in the epithelial cell layer such as villous atrophy and crypt cell hyperplasia. Studies using intestinal explants have shown that activation of T cells by specific antibody or mitogens resulted in crypt hyperplasia [9,10] and villous atrophy [9], suggesting a role for T cells or their secreted cytokines in these effects. Further, it has been suggested that the manifestations of villous atrophy are probably due to the T cell-derived cytokines interferon-gamma (IFN-) and tumour necrosis factor (TNF) [11], but the mechanisms involved in the induction of crypt cell hyperplasia are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Here, there is a clear genetic predisposition associated with human lymphocyte antigen DRQ2 shared by one-third of the population, which only leads to disease in a few. In some, onset of symptoms follows an acute infection (26,27). Experimentally, nonspecifically activating mucosal lymphocytes can result in villus atrophy (26) and may thus precipitate symptomatic disease, which may resolve once the superimposed infection has subsided (26).…”
Section: Estimating the Importance Of Infection In Ibsmentioning
confidence: 99%